Cost of Anti-CD38 Monoclonal Antibodies in Combination With Bortezomib, Lenalidomide and Dexamethasone for the Frontline Treatment of Transplant-Ineligible Patients With Newly Diagnosed Multiple Myeloma in the US - Niodita Gupta-Werner; Vipin Khare; Brian Macomson; Rohan Medhekar (Journal of Health Economics and Outcomes Research)
# Background The efficacy of the combination of bortezomib, lenalidomide, and dexamethasone with daratumumab (DVRd) or isatuximab (IsaVRd) for the frontline treatment of transplant-ineligible (TIE) newly diagnosed multiple myeloma (NDMM) has been demonstrated in clinical trials. However, the treatment cost for DVRd and IsaVRd has not been compared.